1989
DOI: 10.1073/pnas.86.22.8758
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cholesterol or gramicidin on slow and fast motions of phospholipids in oriented bilayers.

Abstract: Nuclear spin-lattice relaxation both in the rotating frame and in the laboratory frame is used to investigate the slow and fast molecular motions of phospholipids in oriented bilayers in the liquid crystalline phase. The bilayers are prepared from a perdeuterated phospholipid labeled with a pair of 'IF atoms at the 7 position of the 2-sn acyl chain.Phospholipid-cholesterol or phospholipid-gramicidin interactions are characterized by measuring the relaxation rates as a function of the bilayer orientation, the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…In contrast, the presence of cholesterol seems to affect the polar head group region to a lesser extent. These observations are in agreement with other 'H, 2H, 13C, and '9F NMR studies (Seiter and Chan, 1973;Lancee-Hermkens and de Kruijff, 1977;Oldfield et al, 1978;Davis, 1983;Peng et al, 1989) that have indicated that the presence of cholesterol markedly restricts the local motions of the phospholipid molecules in unsonicated liposomes. In particular,2H NMR results have shown that the incorporation of cholesterol causes an increase of the quadrupolar splitting of the fatty acyl chains, which can be explained by a decrease in the extent and rate of trans-gauche isomerization (Siminovitch et al, 1988).…”
Section: Spin-lattice Relaxation Times In the Laboratory Frame (Ht1)supporting
confidence: 92%
“…In contrast, the presence of cholesterol seems to affect the polar head group region to a lesser extent. These observations are in agreement with other 'H, 2H, 13C, and '9F NMR studies (Seiter and Chan, 1973;Lancee-Hermkens and de Kruijff, 1977;Oldfield et al, 1978;Davis, 1983;Peng et al, 1989) that have indicated that the presence of cholesterol markedly restricts the local motions of the phospholipid molecules in unsonicated liposomes. In particular,2H NMR results have shown that the incorporation of cholesterol causes an increase of the quadrupolar splitting of the fatty acyl chains, which can be explained by a decrease in the extent and rate of trans-gauche isomerization (Siminovitch et al, 1988).…”
Section: Spin-lattice Relaxation Times In the Laboratory Frame (Ht1)supporting
confidence: 92%
“…One preliminary study has revealed a cross-relaxation pathway between water and a lipid system, where selective irradiation of the water was shown to affect the T I of the lipid (13). Previous NMR studies of lipid vesicles have demonstrated the dependence of cross relaxation and spin diffusion within the lipid on the correlation times as well as the dipolar order parameter, SHH, of the bilayer system (10,11,19,20). As the correlation time increases, the energy conserving "zero quantum" dipoledipole processes will dominate the magnetization exchange pathway ( 10,19).…”
Section: Discussionmentioning
confidence: 97%
“…The phospholipid and the additive were first codissolved in chloroform/ methanol mixture (3:1, vol/vol). The solution was directly deposited onto microscope cover slips, followed by evaporation in vacuum and hydration as described previously (Peng et al, 1988).…”
Section: Sample Preparationmentioning
confidence: 99%
“…Thus, TI, measurements reflect only the averaged properties of the phospholipid molecule in both phases. For a more detailed discussion, see Peng et al (1989).…”
Section: Nmr Measurementsmentioning
confidence: 99%
See 1 more Smart Citation